The Effect of Back Massage on Breastfeeding Mothers Using Lavender Essential Oil on Breast Milk Production At Bpm Wahyu Jl. Pertiwi No. 58 Pond Village, Percut Sei Tuan District in 2021 - Zuidah (Institute of Computer Science (IOCS), 2022)
Breast milk is an emulsion of fat in a solution of protein, lactose and inorganic salts secreted by the mother's mammary glands. Oxytocin is a hormone that affects the lactation process. Oxytocin that reaches the mammary alveoli causes contraction of the myoepithelial cells surrounding the mammary alveoli and lactiferous ducts. Back massage on the cervical 5-6 to the lower shoulder blades stimulates the release of endorphins and oxytocin hormones and increases blood circulation in the breast area. This study uses a pre-experimental type of research, with a One Group pre-test and post-test design. The population in this study were all breastfeeding mothers who were at BPM Wahyu Jl Pertiwi No.58 Pond Village, Percut Sei Tuan District in 2021, the data collected in May-September were 35 people, The sample in this study was purposive sampling technique, with the research technique using the Chi Square test. The results of this study indicate that there is a significant effect on breast milk production in nursing mothers when a back massage is performed using lavender essential oil. The number of breastfeeding mothers after a back massage using Lavender essential oil produced smooth breast milk with a total of 27 mothers (77.14%) whose breast milk was smooth. The results of statistical tests using the Wilcoxon test show that the p value (0.001) < (0.05) means Ho is rejected, so there is a significant effect on breast milk production if breastfeeding mothers are massaged using lavender essential oil at BPM Wahyu Jl Pertiwi No. 58 Pond Village, Percut Sei Tuan District, 2021. .